Ionic liquids as phase transfer catalysts: Enhancing the biphasic extractive epoxidation reaction for the selective synthesis of β-O-glycosides. Issue 38 (20th September 2017) - Santiago, Cintia C.; Lafuente, Leticia; Bravo, Rodolfo; Díaz, Gisela; Ponzinibbio, Agustín
Graphical abstract: Highlights: DMDO generated in situ oxidize endo -glycals under biphasic conditions. DodMImBF4 ionic liquid promoted the direct epoxidation of glycals acting as PTC. β-O-glycosides were synthesized in good yields and high stereoselectivity. Abstract: Ionic liquids promoted the direct epoxidation of glycals acting as PTC. 1, 2-anhydrosugars were prepared by the oxidation of glycals under biphasic conditions with dimethydioxirane generated in situ from oxone/acetone and amphiphilic IL's as catalysts. β-O-glycosides were synthesized in good yields by the nucleophilic ring opening of epoxy carbohydrate derivatives. Also, 3, 4, 6-benzyl protected carbohydrates and β-N-glycosides could be prepare by this method.